Optical enhancement of a printed organic tandem solar cell using diffractive nanostructures - Mayer, Jan; Offermans, Ton; Chrapa, Marek; Pfannmöller, Martin; Bals, Sara; Ferrini, Rolando; Nisato, Giovanni (Optics express, 2018)
Solution processable organic tandem solar cells offer a promising approach to achieve cost-effective, lightweight and flexible photovoltaics. In order to further enhance the efficiency of optimized organic tandem cells, diffractive light-management nanostructures were designed for an optimal redistribution of the light as function of both wavelength and propagation angles in both sub-cells. As the fabrication of these optical structures is compatible with roll-to-roll production techniques such as hot-embossing or UV NIL imprinting, they present an optimal cost-effective solution for printed photovoltaics. Tandem cells with power conversion efficiencies of 8-10% were fabricated in the ambient atmosphere by doctor blade coating, selected to approximate the conditions during roll-to-roll manufacturing. Application of the light management structure onto an 8.7% efficient encapsulated tandem cell boosted the conversion efficiency of the cell to 9.5%.
Gesehen am 23.03.2020